Optimum control and design of a small hydro power plant for agriculture investment in Iraqi desert - Hameed, Jamal Ahmed; Atyia, Thamir Hassan; Jaf, Saba Fadhil Ahmed; Abdulkareem, Zubaidah Ghaze; Hasan, Ghanim Thiab (Institute of Advanced Engineering and Science, 2025)
The aim of this paper is to conduct a mathematical and physical analysis to get a systematic treatment of design parameters and thus optimize water wheels. By today's standards, one finds empirical formulas instead, which take into account the practical experience of previous constructions, estimates of particular wheelbase shapes and sizes. So, based on the basic design and optimization standards for water wheels implementation, this paper attempts to design a water wheel power source in desert areas. Since the water wheels mainly use the gravitational force of water, there is only a slight hydrodynamic power losses. In addition to the high torque due to the large inertia of the water wheel. The obtained results indicate that the optimum operating range of the trailing water wheels is at a diameter of (2-7 m) and the Q water flow of about (0.1 m3/s). So, it can conclude that the implementing design has good efficiency and offer an economic benefit when use for the agriculture investment in desert areas.